2019
DOI: 10.1177/1087054719875787
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity and Addiction Severity Differences in Patients With ADHD Seeking Treatment for Cannabis or Cocaine Use Disorders

Abstract: Objective: The objective of this study was to compare psychiatric comorbidity and consumption-related variables in ADHD patients seeking treatment for cocaine, cannabis, or both. Method: Assessment was conducted using European Addiction Severity Index (EuropASI), Conners’ Adult ADHD Diagnostic Interview (CAADID), Structured Clinical Interview for DSM Disorders (SCID), Adult Self-Report Scale (ASRS), Wender Utah Rating Scale (WURS), Barratt Impulsiveness Scale-11 (BIS-11), and FIDI, with statistical analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
1
5
0
1
Order By: Relevance
“…We also found evidence of genetic correlations between all traits considered in the study, namely ADHD, smoking initiation, age of smoking initiation, cigarettes per day, smoking cessation, alcohol or cocaine dependence and lifetime cannabis use. These results are in agreement with extensive literature showing poorer smoking outcomes and higher rates of polysubstance use and comorbidity between ADHD and SUD (Capusan et al, 2019; Hayley et al, 2017; Martínez‐Luna et al, 2019; van Emmerik‐van Oortmerssen et al, 2014) and add additional evidence for a common genetic background among these phenotypes (Du Rietz et al, 2018; Wimberley et al, 2019, Wilens, 2007; Vink et al, 2014; Chang et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…We also found evidence of genetic correlations between all traits considered in the study, namely ADHD, smoking initiation, age of smoking initiation, cigarettes per day, smoking cessation, alcohol or cocaine dependence and lifetime cannabis use. These results are in agreement with extensive literature showing poorer smoking outcomes and higher rates of polysubstance use and comorbidity between ADHD and SUD (Capusan et al, 2019; Hayley et al, 2017; Martínez‐Luna et al, 2019; van Emmerik‐van Oortmerssen et al, 2014) and add additional evidence for a common genetic background among these phenotypes (Du Rietz et al, 2018; Wimberley et al, 2019, Wilens, 2007; Vink et al, 2014; Chang et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Second, information on childhood ADHD was not systematically assessed, because of the absence of informants and the underdiagnosis of this condition [13]. A retrospective screening questionnaire for childhood ADHD, for example, the Wender Utah Rating Scale could assess potential childhood ADHD in adult patients without information from third parties and overcome this limitation in future studies [48][49][50]. Third, DDDE and poly-drug use were based on patients' self-report and not confirmed by urine or serum toxicology.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity between ADHD and SUDs is associated with increased cannabis use. Numerous studies have shown that individuals with ADHD and SUDs have an earlier onset of substance use and cannabis use [ 11 , 24 , 55 , 56 ]. Early cannabis use (ie, during adolescence) is linked to the disruption of functional circuit maturation-refinement [ 14 , 56 ].…”
Section: Cannabis Use Disordersmentioning
confidence: 99%
“…Numerous studies have shown that individuals with ADHD and SUDs have an earlier onset of substance use and cannabis use [ 11 , 24 , 55 , 56 ]. Early cannabis use (ie, during adolescence) is linked to the disruption of functional circuit maturation-refinement [ 14 , 56 ]. Research indicates that 33.19–38.10% of adolescents with CUDs have a comorbid ADHD diagnosis.…”
Section: Cannabis Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation